PERAN KOMPETENSI STAF ADMINISTRASI DALAM IMPLEMENTASI MANAJEMEN KEARSIPAN DI SMA NEGERI 1 DRAMAGA - Fitriani, Neng Siska Fitriani; Rahmawati, Ima; Ihsan, Muzhir; Suryanto, Suryanto (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
This study aims to determine the role of administrative staff competence in the implementation of archival management at SMA Negeri 1 Dramaga. This research is a field research and literature study using a qualitative descriptive approach. Data collection uses literature, observation, interviews, and documentation. The data analysis technique in this study was carried out in two stages where the first stage analyzed during the activity, namely by observation, interview, and documentation, the second stage was the analysis after the activity was carried out which had three stages, namely data reduction, presentation, and conclusion drawing. The results showed that the application of administrative staff competencies can provide optimal and effective and efficient performance so that work can be completed quickly and can improve the quality of education.